Community Development by Increasing Awareness of Product Innovation and Halal Certificate in Cibodas, Pandeglang - Mangara, Togi Haidat; Setyadi, Sugeng; Desmawan, Deris; Syaifudin, Rizal (EQUATOR SINAR AKADEMIA, 2024)
This article shows the implementation of community service activity in Cibodas Village which is the socialization of product innovation and halal certification with local entrepreneurs as the target audience. The problem found prior to this activity is the lack of understanding from the local entrepreneurs regarding how to make their product more attractive and how to process the halal certification. With this activity, the local entrepreneurs begin to have a basic knowledge of what kind of innovation they can do for their products and also how to process the halal certification.This article shows the implementation of community service activity in Cibodas Village which is the socialization of product innovation and halal certification with local entrepreneurs as the target audience. The problem found prior to this activity is the lack of understanding from the local entrepreneurs regarding how to make their product more attractive and how to process the halal certification. With this activity, the local entrepreneurs begin to have a basic knowledge of what kind of innovation they can do for their products and also how to process the halal certification.